The course of the Orphan Stream in the Northern Galactic hemisphere traced with Gaia DR2. Issue 1 (27th March 2019) - Fardal, Mark A; van der Marel, Roeland P; Sohn, Sangmo Tony; del Pino Molina, Andres
Abstract: The Orphan Stream is one of the most prominent tidal streams in the Galactic halo. Using data on red giants, RR Lyrae, and horizontal branch stars from Gaia and other surveys, we determine the proper motion of the Orphan Stream over a path of more than 90° on the sky. We also provide updated tracks for the sky position, distance, and radial velocity of the stream. Our tracks in these latter dimensions mostly agree with previous results. However, there are significant corrections to the earlier distance and latitude tracks as the stream approaches the Galactic disc. Stream stars selected with three-dimensional kinematics display a very tight red giant sequence. Concordantly, we find that applying a proper motion cut removes the most metal-rich stars from earlier spectroscopic samples of stream stars, though a significant dispersion remains, indicating a dwarf galaxy origin. The deceleration of the stream towards its leading end suggests a circular velocity of$\sim \!200 \, km\, s^{-1}$ at a galactocentric radius$\sim \!30 \, kpc$, consistent with other independent evidence. However, the track of the stream departs significantly from an orbit; the spatial track does not point along the same direction as the velocity vector, and it exhibits a lateral wiggle that is unlikely to match any reasonable orbit. The low metallicity and small dispersion of the stream in the various coordinates point to a progenitor with a relatively low dynamical mass$\sim \!10^8 \, M_{\odot }$ .